Assessment of the Sustainability of the Socio-economic Development of the Regions in Russia - R. V. Fattakhov; M. M. Nizamutdinov; V. V. Oreshnikov (Мир новой экономики, 2019)
Introduction. The regions of Russia are not only heterogeneous in terms of the current state but also differ in the prevailing trends in the key parameters of their future development. Some of them, possessing significant economic potential, risk losing stability due to ongoing social processes and vice versa. The purpose of the study is to assess the sustainable development of the Russian Federation regions, to identify typical regions, including implementation of the main priority of the Spatial Development Strategy of Russia until 2025 — to uncover the socio-economic potential of the territories and their sustainable development through economic specialisation regions.Methods. In the framework of solving the problem of choosing typical regions of Russia according to the level of sustainability of socio-economic development, we formed a database of indicators for the period from 2010 to 2016. The 8th indicators describe the financial and economic component of development, the social component — by the 14th indicators, the environmental one — by the 3rd indicators. The ranking of regions was carried out in three stages — the consideration of particular indicators, their unification into groups and the study of generalised values. For the identification of typical regions, we applied the clustering method.Results. Approbation of the approach showed that the high position of the region in one of the considered areas of analysis does not always correlate with the level in other indicators. The magnitude of the dispersion in general increases with the transition from the leading regions to the outside regions. Cluster analysis revealed four groups of regions. The first cluster is characterised by the predominance of the economic component. The second cluster is characterised by the absence of a significant imbalance between the directions. The third cluster is characterised by better dynamics of financial and economic indicators against the background of relatively good positions in the social and environmental spheres. The fourth cluster is represented by subjects of the Russian Federation, in which there are significant results in the field of improving the environmental component. Based on the cluster analysis, typical regions were selected — the Republic of Ingushetia, the Samara Region, the Republic of Tatarstan and the Vladimir Region, respectively.Discussion. The obtained results can be applied when making a forecast of the socio-economic development of the regions of the Russian Federation and indicators of their sustainability in the medium term.